THE ROLE OF ENCOUNTER PROJECT ON STUDENTS’ MOTIVATION TO LEARN TO SPEAK ENGLISH - Solihin; Aris Dwi Intan Aprianti; Dita Rezkia Utami; Mayang Sari (STKIP Paracendekia NW Sumbawa, 2023)
This study was aimed at finding out the role of encounter project on students’ motivation to learn to speak English. Two research questions led this study: 1) What is the role of encounter project on students’ motivation to learn to speak English? 2) How are the students’ efforts to learn to speak English as the consequence of their speaking motivation after doing encounter project? Mixed-methods approach was applied. The genre of the qualitative method was case study, in addition to the descriptive quantitative. The number of the participants of this study was 15 students who continuously went to talk with English speaking tourists upon the completion of their “encounter project”. The results show that the role of encounter project is to lead the students to have not only instrumental motivation in learning to speak English, but also wider expectations named integrative motivation. The students’ efforts to learn to speak English as the consequence of their speaking motivation after conducting encounter project are in forms of their activities outside and inside the classroom. Classroom activities are in forms of their attention to classmates’ and lecturers’ accents, whether their accent refers to Australian, American or British. They also take notes of the terms used in the conversations among student-student and student-lecturer. Outside classroom efforts are in forms of their consistency to meet tourists, organize English camps, run speaking club and English goes to school. They also collected videos regarding the accents and different uses of the terms among Australian, American and British.